Akuntabilitas dan Transparansi Laporan Keuangan Sebagai Faktor Penentu Tingkat Kepercayaan Muzaki terhadap LAZIS - Mentari Ariesta Iyonu (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to answer the formulation of the problem of whether the transparency and accountability of financial reports affect the level of Muzaki's trust in the amil zakat infaq and sadaqah (LAZIS) institution in Gorontalo Regency. This study uses a quantitative approach and uses primary data sources. Primary data was collected by distributing questionnaires boldly and attractively to muzaki who pay zakat either through LAZIS managed by the government or privately managed LAZIS in Gorontalo District. The sampling method used was nonprobability sampling, and the research obtained was 100 respondents. Multiple linear regression analysis technique is used to analyse the research data. The study's results prove that transparency and accountability of financial reports positively influence the level of Muzaki's trust in Gorontalo District. Of the two research variables, transparency of financial reports is the most dominant variable influencing the level of muzaki trust in Gorontalo District.